The effects of smoking on inflammatory and angiogenic pathways in the retina of mice - Wang, Feng; Justus Liebig University Giessen (My University, 2022)
Cigarette smoke has been identified as a major risk factor for the development of age-related macular degeneration (AMD). As an alternative of conventional cigarette (C-cigarette), electronic cigarette (E-cigarette) has been rapidly promoted and used globally. The increasing usage of E-cigarette raises concerns with regard to long-term consequences related to retinal tissue. In the present study, a controlled study in mice models was conducted to probe the comprehensive effects of E-cigarette on retina, RPE and choroid tissues by (1) comparing the effect of C-cigarette smoke and E-cigarette smoke on retina; (2) determining the effects of E-cigarette vapor on the RPE and analyzing the changes with regard to inflammatory and angiogenic mediators in retina/RPE/choroid. The data showed that C-cigarette smoke exposure promoted an inflammatory reaction in the retina in vivo. Mice exposed to E-cigarette (nicotine-free) vapor developed inflammatory and angiogenic reactions more pronounced in RPE and choroid, while nicotine-containing E-cigarette vapor caused even a more serious reaction. Both, inflammatory and pro-angiogenic reactions increased with the extension of exposure time. These results demonstrate that exposure to C-cigarette smoke is harmful to the retina. Likewise, the exposure to E-cigarette vapor (with or without nicotine) increases the occurrence and progression of inflammatory and angiogenic stimuli in the retina, which might be similar effects causing the onset of wet AMD in humans.
Keywords: C-cigarette smoke; E-cigarette vapor; Inflammatory reaction; Angiogenesis; AMD; ddc:610